EFEKTIVITAS UNGGAHAN FOTO DI AKUN INSTAGRAM @INDOTRAVELLERS.CO TERHADAP MINAT BERLIBUR KOMUNITAS BACKPACKER MALANG - Muhammad Ikbal; Mochammad Abdul Ghofur (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Instagram is used as a promotional media for photos or videos aimed at providing information. Photos uploaded on Instagram are able to tell the condition of tourist attractions, provide a list of selected tours and provide tourist information according to the facts so as to foster interest in vacationing on followers who have a hobby of vacationing especially in Malang Backpacker community. The purpose of this study is to determine the effectiveness of Instagram @ Indotravellers.co accounts for the interest in vacationing Malang Backpacker Community. The study was conducted using qualitative methods. The informants in this study were 5 people consisting of community leaders, public relations officers and active members who suggested interesting tourist information to visit the Malang Backpacker Community. Data collection techniques are carried out by interview. Data analysis method used is descriptive method. The effectiveness of Instagram @ Indotravellers.co accounts is known from the many follwer numbers, uploading good quality photos and matching tourist themes taken when the weather supports. The results of uploading photos of the latest, natural and complete tourist objects can foster interest in vacation followers. Keywords: Photo Upload Effectiveness, @ Indotravellers.co and Vacation Interests Abstrak: Instagram digunakan sebagai media promosi hasil foto atau video yang bertujuan memberi informasi. Foto yang diunggah di Instagram mampu menceritakan kondisi objek wisata, memberikan daftar wisata pilihan dan memberikan informasi wisata sesuai fakta sehingga menumbuhkan minat berlibur pada follower yang memiliki hobi berlibur terutama pada komunitas Backpacker Malang. Tujuan penelitian ini adalah mengetahui efektivitas akun Instagram @Indotravellers.co terhadap minat berlibur Komunitas Backpacker Malang. Penelitian dilakukan dengan menggunakan metode kualitatif. Informan dalam penelitian ini sebanyak 5 orang terdiri dari ketua komunitas, pengurus bagian humas dan anggota yang aktif menyarankan informasi wisata menarik untuk dikunjungi Komunitas Backpacker Malang. Teknik pengumpulan data dilakukan dengan wawancara. Metode analisa data yang di gunakan yaitu metode deskriptif. Efektivitas akun Instagram @Indotravellers.co diketahui dari jumlah follwer banyak, mengunggah foto yang berkualitas baik dan sesuai tema wisata yang diambil saat cuaca mendukung. Hasil unggahan foto objek wisata yang terbaru, natural dan lengkap mampu menumbuhkan minat berlibur follower. Kata kunci: Efektivitas Unggahan Foto, @Indotravellers.co dan Minat Berlibur